2020
DOI: 10.1111/iju.14231
|View full text |Cite
|
Sign up to set email alerts
|

Circadian clock and cancer: From a viewpoint of cellular differentiation

Abstract: Abbreviations & Acronyms AML = acute myeloid leukemia ccg = clock-controlled gene DNMT1 = DNA methyltransferase 1 E19 = embryonic day 19 ES = embryonic stem iPS = induced pluripotent stem MEF = mouse embryonic fibroblast MRT = malignant rhabdoid tumor OSKM = Oct3/4, Sox2, Klf4 and c-Myc Per2 Luc = Per2::Luciferase SCN = suprachiasmatic nucleus SMG = submandibular gland TTFL = transcriptionaltranslational feedback loop UPR = unfolded protein response Correspondence: KazuhiroAbstract: The circadian clock control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 100 publications
(125 reference statements)
0
22
0
Order By: Relevance
“…We selected 24 CCGs that contribute to circadian rhythm and summarized their location on chromosomal [38][39][40] ( Figure 1A). Then, the expression profile of CCGs in glioma was also depicted.…”
Section: Expression Profile Of Circadian Clock Genes and Clinical Fmentioning
confidence: 99%
“…We selected 24 CCGs that contribute to circadian rhythm and summarized their location on chromosomal [38][39][40] ( Figure 1A). Then, the expression profile of CCGs in glioma was also depicted.…”
Section: Expression Profile Of Circadian Clock Genes and Clinical Fmentioning
confidence: 99%
“…However, these studies have also revealed that not everything has a clock. Embryonic stem cells, which can develop into almost any cell type, do not keep time, and many cancer cells do not keep a regular rhythm: a modified proliferation and differentiation pattern is common to both stem and cancerous cells (Tsuchiya et al 2020).…”
Section: The Lesson From the Entraining Of The Clock And Cell Cycle Omentioning
confidence: 99%
“…The study of the core-clock, clock-controlled genes and their related biological and molecular processes, in human subjects and animal models, has strongly contributed to gaining insights into the circadian dysregulation underlying severe diseases including cancer [ 204 , 205 , 206 , 207 , 208 , 209 , 210 ]. Determining the circadian time and the circadian profile of a healthy subject and detecting possible abnormalities or malfunctions of the biological clock which may trigger disease or increase its severity remains a challenging task, in particular when asking for a mechanistic understanding on which clinical trials may be based.…”
Section: Discussion Limitations and Conclusionmentioning
confidence: 99%